2014
DOI: 10.1371/journal.pcbi.1003450
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics Decouples Mutational from Environmental Robustness. Did It Also Facilitate Multicellularity?

Abstract: The evolution of ever increasing complex life forms has required innovations at the molecular level in order to overcome existing barriers. For example, evolving processes for cell differentiation, such as epigenetic mechanisms, facilitated the transition to multicellularity. At the same time, studies using gene regulatory network models, and corroborated in single-celled model organisms, have shown that mutational robustness and environmental robustness are correlated. Such correlation may constitute a barrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…Intriguingly, our results show a similar pattern in VSV, where the decoupling of genetic robustness and thermostability may be related to the evolution of antigenic variation. Others have proposed decoupling mechanisms that may be relevant for other systems, such as oligomerization [71] or epigenetic modification [72]. …”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, our results show a similar pattern in VSV, where the decoupling of genetic robustness and thermostability may be related to the evolution of antigenic variation. Others have proposed decoupling mechanisms that may be relevant for other systems, such as oligomerization [71] or epigenetic modification [72]. …”
Section: Discussionmentioning
confidence: 99%
“…Their catalytic signatures are well-characterized; PRC2 trimethylates histone H3K27 into H3K27me3; this modified histone is bound by PRC1, which in turn ubiquitylates histone H2A. Extensive study on the evolution and conservation of PRC1 and PRC2 has suggested that expansion and diversification of PcG proteins contributed to the complexity of multicellular organisms (Trojer & Reinberg 2006;Whitcomb et al 2007;Köhler & Villar 2008;Gombar et al 2014).…”
Section: Blue Is Related To the Origin Of Multicellularitymentioning
confidence: 99%
“…The chromatin landscape consists of DNA, histones, and other associated proteins and RNAs, and plays a fundamental role in development, cellular memory, and integration of external signals. As a unique feature of the eukaryotic cell, it is closely tied to the evolution of eukaryotes, both regarding their origin and the major transition(s) to multicellularity (Newman 2005;Aravind et al 2014;Gombar et al 2014;Penny et al 2014;Miyamoto et al 2015;Sebé-Pedrós et al 2017). At a basic level, chromatin is responsible for maintenance, organization, and correct use of the genome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there is no definitive method for introducing the epigenetic process because the precise molecular process of histone modification is difficult to implement in a model with gene expression dynamics. However, it is possible to model the influence of the epigenetic process on expression dynamics phenomenologically [34][35][36][37][38]. The epigenetic process tends to fix the expression state; for example, when a given gene is expressed for a given period, its expression tends to become fixed, and when it is not expressed for a given period, it remains silenced.…”
Section: Differentiation From the Pluripotent State With Epigenetic Mmentioning
confidence: 99%